13th CONTECSI - International Conference on Information Systems and Technology Management - Riccio, Edson Luiz (Journal of Information Systems and Technology Management, 2015)
The 13th International Conference on Technology and Information Systems Management CONTECSI is an event focusing Technology and Information Systems Management under a multidisciplinary view. CONTECSI aims at putting together academics and professionals involved in IT and Systems management for a state-of-the-art discussion. International researchers are expected to contribute for the integration between the academic and the professional communities. The Conference welcomes papers submission for presentation and panel discussions. Major topics on interest include, but are not limited to: Information Society, Open Systems, Systems Interfacing and Integration, Wireless Computing, Entrepreneurship in IT and IS, Accounting Information Systems, E-Commerce / E-Business, Software Engineering, ERP Systems, Financial Management in Information Systems, IT Strategic Management. All papers will be subject to a blind review process and full papers will be published (CD) in the Conference Proceedings.